The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.3390/foods12122315
|View full text |Cite
|
Sign up to set email alerts
|

Plant Antimicrobials for Food Quality and Safety: Recent Views and Future Challenges

Abstract: The increasing demand for natural, safe, and sustainable food preservation methods drove research towards the use of plant antimicrobials as an alternative to synthetic preservatives. This review article comprehensively discussed the potential applications of plant extracts, essential oils, and their compounds as antimicrobial agents in the food industry. The antimicrobial properties of several plant-derived substances against foodborne pathogens and spoilage microorganisms, along with their modes of action, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 293 publications
0
26
0
Order By: Relevance
“…Similar result has been reported by Singh et al [ 24 ] exhibiting the inhibition of fumonisin isolated from maize kernels by clove essential oil nanoemulsion. The antimycotoxigenic activity of essential oil and nanoformulations has also been associated with the inhibition of ROS production and detoxification/activation of biotransformation pathway, hence disrupting the signal transduction in mycotoxin synthesis [ 83 ]. Therefore, AGEO-Ne could be used as controlled and innovative delivery vehicle for inhibition of fumonisin mediated deterioration of stored rice samples.…”
Section: Resultsmentioning
confidence: 99%
“…Similar result has been reported by Singh et al [ 24 ] exhibiting the inhibition of fumonisin isolated from maize kernels by clove essential oil nanoemulsion. The antimycotoxigenic activity of essential oil and nanoformulations has also been associated with the inhibition of ROS production and detoxification/activation of biotransformation pathway, hence disrupting the signal transduction in mycotoxin synthesis [ 83 ]. Therefore, AGEO-Ne could be used as controlled and innovative delivery vehicle for inhibition of fumonisin mediated deterioration of stored rice samples.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were found by Peighambardoust et al [ 68 ], who suggested that Yarrow plant EO, rich in eucalyptol and camphor, could block the growth of PTC (3.97–4.65 log CFU/g) in chicken meat until 15 days of storage. Previous studies suggested that these bioactive compounds could exert their bactericidal activities by interacting with lipid bilayers, resulting in multiple mechanisms of action, including the perturbation of cell membrane functionality and integrity, as well as the inhibition of bacterial enzymes involved in ATP production and genetic material replication and transcription [ 69 , 70 ]. Merghni et al [ 71 ] demonstrated that eucalyptol could damage the membrane integrity and induce ROS-mediated oxidative stress in MRSA cells.…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, they are derived from renewable sources, rendering them environmentally friendly compared to synthetic chemicals. Additionally, plant antimicrobials are generally considered safe for consumption and do not leave behind harmful residues, addressing concerns related to chemical residues in food products [27]. Testing the preservative activity of plant extracts against milk pathogens using isolated milk pathogenic strains and a sterilized milk medium is a valuable approach for assessing the antimicrobial potential of these extracts.…”
Section: Preservative Activity In Sterilized Milk Mediummentioning
confidence: 99%